Shortening Fermentation Period and Quality Improvement of Fermented Fish, Chouguiyu, by Co-inoculation of Lactococcus lactis M10 and Weissella cibaria M3 - Bao, Ruiqi; Liu, Sasa; Ji, Chaofan; Liang, Huipeng; Yang, Song; Yan, Xiaoming; Zhou, Yingqin; Lin, Xinping; Zhu, Beiwei (Frontiers in Microbiology, 2018)
Chouguiyu, a Chinese traditional fermented fish, is famous for its uniquely strong odor and desirable taste. However, traditional spontaneous fermentation often resulted in contamination and unstable quality of products. In this study, individual or conjunctive inoculation of two indigenous lactic acid bacteria (LAB), Lactococcus lactis M10 and Weissella cibaria M3, was tested for their effect on improving Chouguiyu’s quality. It was shown that inoculation would not affect the system’s pH, while increased the total bacteria count and lactic acid bacteria amounts. Matrix-assisted laser desorption/ionization time-of-flight mass (MALDI-TOF) analysis results revealed that Lactoc. lactis M10 and W. cibaria M3 could quickly occupy a dominant position in the ecosystem, and Lactoc. lactis M10 played an important role in the control of spoilage bacteria. Volatile basic nitrogen (TVB-N), thiobarbituric acid reactive substances (TBARS), and biogenic amines results also showed that Lactoc. lactis M10 had a positive effect on improving the product’s quality. Co-inoculation of Lactoc. lactis M10 and W. cibaria M3 could promote the formation of flavor according to the E-nose and gas chromatography-mass spectrometer (GC-MS) analyses, especially for the aroma-active and key volatile compounds. PCA plots of E-nose and hierarchical clustering analysis of GC-MS profiles revealed that the co-inoculation sample at the fifth day (LW5) was the most similar to the natural fermentation sample at the seventh day (C7). The overall acceptance of LW5 was also the closest to that of C7 in sensory evaluation. In conclusion, mixed starter culture was shown to have a good effect on improving product quality and enhancing flavor with fermentation time shortened by 29%.